Ion Ni2+ di Dalam Air; Pembentukan Fungsi Potensial Intermolekul - Bambang Setiaji; Tutik Arindah (Universitas Gadjah Mada, 2002)
Pair potential function of Ni2+-H2O system has been constructed by ab initio method at UHF (Unrestricted Hartre-Fock) level. The basis sets used for energy interaction calculation were LANL2 Double-z ECP of Hay and Wadt for Ni2+ and Double-z Polarization of Dunning for H2O. Construction of pair potential function was done by collecting more than 3000 energy points that represent all interactions of Ni2+ ion and water. The pair potential function of Ni2+-H2O resulted of fitting proses by standard deviation of 3,25 kcal/mol is where AiM, BiM, CiM and DiM are fitting parameter of Ni2+-O or Ni2+-H, riM is distance of i atoms between H2O and Ni2+, q is charge of i atoms of H2O resulted by Mulliken population analysis, and qM is net charge of Ni2+ ion.